The first Nocticola Bolivar 1892 (Blattodea: Nocticolidae) from New Guinea - Lucañas, Cristian C.; Bláha, Martin; Rahmadi, Cahyo; Patoka, Jiří (Zootaxa, 2021)
A new species of highly troglobitic cockroach, Nocticola baumi n. sp., is described from limestone caves of Papua Province, Indonesia. The new species is the first Nocticola reported in New Guinea island and differs from other known Nocticola spp. by the combination of the following characters: compound eyes and ocelli absent, tegmina fully developed extending beyond the abdomen, hind wings absent, legs extremely long. The discovery of the genus on New Guinea bridges the gap between Oriental and Australian distribution of the genus and stresses the unknown diversity of the genus.